1986
DOI: 10.1007/bf00688040
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of muscle fiber types in regenerating chicken muscles following cross-reinnervation

Abstract: Slow-tonic anterior latissimus dorsi (ALD) and fast-twitch posterior latissimus dorsi (PLD) muscles of 7 to 10-day-old White Leghorn chickens were crushed and allowed to be reinnervated by their own nerve, or crushed and transplanted to the other side and allowed to be reinnervated by the nerve of the side to which they were transplanted. Following transplantation, changes in the weight of the muscle, fiber-type composition and innervation pattern during regeneration were investigated. Normal growth rate of PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Such change is detectable as early as 1 h after a single bout of exercise (57,58). White‐to‐red fiber conversion has been described in response to exercise (59) and other interventions associated with increased intracellular energetic expenditure such as electrical stimulation (60), cross‐reinnervation (61), a diet rich in carnitine, carnosine and taurine (62), beta adrenergic stimulation (63), androgen receptor antagonism (64) and mild heat stress (65). However, the results of this study are limited to describing an up‐regulation of oxidative capacity as measured by cytochrome oxidase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Such change is detectable as early as 1 h after a single bout of exercise (57,58). White‐to‐red fiber conversion has been described in response to exercise (59) and other interventions associated with increased intracellular energetic expenditure such as electrical stimulation (60), cross‐reinnervation (61), a diet rich in carnitine, carnosine and taurine (62), beta adrenergic stimulation (63), androgen receptor antagonism (64) and mild heat stress (65). However, the results of this study are limited to describing an up‐regulation of oxidative capacity as measured by cytochrome oxidase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all the fibers of the ALD and pectoralis muscles are shown to be slow tonic fibers (98%, Kikuchi et al, 1986) and fast twitch fibers (98%, Nonaka and Sugita, 1981), respectively. ALD muscle fiber was more sensitive than the pectoralis muscle fiber to Ca2+, Sr2+, and Ba2+ for contraction, especially to the latter two ions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, direct electrical stimulation of denervated ALD was ineffective in preventing the postdenervation changes in AChE-molecular-form distribution. It has been reported that denervated ALD muscle does not respond as well to electrical stimulation as PLD muscle does, with respect to myosin light chains and to oxidative activity [19]; furthermore, it exhibits less plasticity for transformation after cross-reinnervation experiments [20]. The differential response of ALD muscle to denervation, cross-reinnervation and to direct electrical stimulation emphasizes the existence of intrinsic differences between fast PLD and slow ALD muscles.…”
Section: Discussionmentioning
confidence: 99%